Commuting Time and the Gender Gap in Labor Market Participation - Lídia Farré; Jordi Jofre-Monseny; Juan Torrecillas (Institute of Labor Economics (IZA), 2020)
This paper investigates the contribution of increasing travel times to the persistent gender gap in labor market participation. In doing so, we estimate the labor supply elasticity of commuting time from a sample of men and women in US cities using microdata from the Census for the last decades. To address endogeneity concerns, we adopt an instrumental variables approach that exploits the shape of cities as an exogenous source of variation for travel times. Our estimates indicate that a 10 minutes increase in commuting decreases the probability of married women to participate in the labor market by 4.6 percentage points. In contrast, the estimated effect on men is small and statistically insignificant. We also find that women with children and immigrant women originating from countries with more gendered social norms respond the most to commuting time variations. This evidence suggests that the higher burden of family responsibilities supported by women may magnify the negative effect of commuting on their labor supply. From our findings, we conclude that the increasing trend in travel times observed in the US and in many European countries during the last decades may have contributed to the persistence of gender disparities in labor market outcomes.
Keywords: R41; J01; J16; J22; 330; commuting time; labor supply; gender roles; family responsibilities; city shape